Penggambaran Watak Tokoh Film Pendek “Lenyap Dalam Sunyi” Sutradara Muhammad Fajruchi K - Surya Darma (Lembaga Pengembangan Kinerja Dosen, 2022)
The film Lenyap dalam Sunyidirected by Muhammad Fajruchi K is a film produced by Fisabilillah Production which won the 2016 Bandung Islamic Film Festival at Pasundan University, Bandung. The purpose of this research is to analyze the characterization of the short film Lenyap dalam Sunyiusing Roland Barthes' semiotic analysis. The meaning of the denotation related to the depiction of the film characters Vanishing in Silence appears in scene 1 with the main characters Prana, and Bardi with the boarding house setting in the morning, then the supporting characters, namely Ziya and Sukma, appear in scenes 4 and 5, scenes meeting at the campus park. The connotative meaning that appears in the character description of the film Lenyap dalam Sunyiis that the character Bardi is a religious person, Bardi is a figure who always reminds Prana in terms of kindness. Prana is a young man who is energetic, looks fashionable, and likes poetry (a poetic person), while Ziya is a Muslim woman, marked by a syar'i dress that covers her nakedness. Ziya is a cousin of Bardi, while Sukma is a symbol of a Muslim woman who is characterized by wearing a khimar and syar'i robe that covers her genitals. Sukma's character is different from Ziya, the depiction of Sukma's character is an energetic woman who seems shy. The myth in this study is the reality that occurs in society that everyone has different characters according to the upbringing of both parents, as well as their education.